2019
DOI: 10.3390/cells8091008
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Metabolism and Surveillance Quartet in the Major Histocompatibility Complex

Abstract: At the central region of the mammalian major histocompatibility complex (MHC) is a complement gene cluster that codes for constituents of complement C3 convertases (C2, factor B and C4). Complement activation drives the humoral effector functions for immune response. Sandwiched between the genes for serine proteinase factor B and anchor protein C4 are four less known but critically important genes coding for essential functions related to metabolism and surveillance of RNA during the transcriptional and transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 118 publications
0
11
0
Order By: Relevance
“…Whereas the HLA class I and class II genomic regions encode the highly polymorphic gene complex of the HLA class I and HLA class II genes, the class III region consists of many different non-HLA genes that are involved in stress response ( HSPA1A, HSPA1B and HSPA1L ), complement cascade ( C4A, C4B, C2, CFB ), immune regulation ( NFKBIL1, FXBPL and DDX39B ), inflammation (LTA, LTB, LST1, ABCF1, AIF1, NCR3 and TNF), leukocyte maturation ( LY6G5B, LY6GSC, LY6G6D, LY6G6E and LY6G6C ), and regulation of T cell development and differentiation ( BTNL2 ) 4 , 36 . Recently, Zhou et al showed that a quartet of MHC class III genes ( NELF-E, SKIV2L, DXO and STK19 ) are involved with the metabolism and surveillance of RNA during the transcriptional and translational processes of gene expression 37 . The class II region also contains some proteosome-processing and peptide antigen transportation non-HLA genes such as PSMB8 , PSMB9, TAP1 , and TAP2 .…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the HLA class I and class II genomic regions encode the highly polymorphic gene complex of the HLA class I and HLA class II genes, the class III region consists of many different non-HLA genes that are involved in stress response ( HSPA1A, HSPA1B and HSPA1L ), complement cascade ( C4A, C4B, C2, CFB ), immune regulation ( NFKBIL1, FXBPL and DDX39B ), inflammation (LTA, LTB, LST1, ABCF1, AIF1, NCR3 and TNF), leukocyte maturation ( LY6G5B, LY6GSC, LY6G6D, LY6G6E and LY6G6C ), and regulation of T cell development and differentiation ( BTNL2 ) 4 , 36 . Recently, Zhou et al showed that a quartet of MHC class III genes ( NELF-E, SKIV2L, DXO and STK19 ) are involved with the metabolism and surveillance of RNA during the transcriptional and translational processes of gene expression 37 . The class II region also contains some proteosome-processing and peptide antigen transportation non-HLA genes such as PSMB8 , PSMB9, TAP1 , and TAP2 .…”
Section: Introductionmentioning
confidence: 99%
“…The 18 papers gathered together in this Special Issue highlight the enormous genetic diversity and broad complexity of the MHC regulatory system and why its genomic structure and function is continuously under scientific investigation. These articles provide new insights as well as confirm some of the more tenuous and/or established beliefs about the genetic and biological roles of the MHC [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. More importantly, many of these articles point MHC researchers and scholars in new directions where technical developments and research can greatly improve our knowledge and concepts of the structure and function of the MHC genomic region, especially as functional haplotypes in humans and all the other vertebrate species on the planet that thrive or are in danger of extinction.…”
Section: Discussionmentioning
confidence: 58%
“…While three reviews of the MHC structure and function focus mostly on the MHC classical and nonclassical Class I and II genes [17,18,19], one review [20] and a research article [22] in this Special Issue specifically describe some of the genes in the MHC Class III region that are associated with the innate immune system, complement activation, inflammation and regulation of immunity [1,2,3,4]. Zhou and co-authors reviewed a cluster of four genes NELF-E, SKIV2L, DXO and STK19 (the NSDK cluster) in the human MHC Class III region that are involved in RNA metabolism and surveillance during the transcriptional and translational processes of gene expression [20]. These four genes seem to engage in the surveillance of host RNA integrity, in the destruction and turnover of faulty or expired RNA molecules or RNA viruses, and in the fine-tuning of innate immunity.…”
Section: Mhc Genomics Functions and Diseases From Humans To Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…(A) A simplified genetic map of the human leukocyte antigen (HLA) on the short arm of chromosome 6 highlighting genes relevant to immune response and inflammation. (B) Gene copy number variations (CNVs) of the RP-C4-CYP21-TNX (RCCX) modules ( 3 , 5 , 6 ). Haplotypes with one to five RCCX modules are shown.…”
Section: Introductionmentioning
confidence: 99%